Danio aesculapii, a new species of danio from south-western Myanmar (Teleostei: Cyprinidae) - Kullander, Sven O.; Fang, Fang (Zootaxa, 2009)
Danio aesculapii, new species, is described from small rivers on the western slope of the Rakhine Yoma in south-western Myanmar. It is superficially similar to D. choprae from northern Myanmar in having a series of vertical bars anteriorly on the side, but differs from it and other species of Danio in having six instead of seven or more branched dorsal-fin rays, and from all other species of Danio except D. erythromicron and D. kerri in having 12 instead of 10 or 14 circumpeduncular scale rows.